Quality of life and symptomatology after high intensity focused ultrasound treatment for uterine fibroids - Van der Merwe, Melissa (My University, 2021)
Uterine leiomyomas (ULs) are the most frequently occurring benign tumours of the female genital tract in premenopausal women. A higher prevalence of larger and multiple ULs is found in African women, which are typically more symptomatic. Women affected by ULs may display numerous types of symptoms impacting one’s quality of life. A novel non-surgical modality explored for the treatment of ULs is the ultrasound guided high-intensity focused ultrasound (USgHIFU). In 2002, Spies et al, developed the Uterine Fibroid Symptom and Health Quality of Life (UFS-HQOL) questionnaire (8 symptom questions and 29 HQOL questions) in order to act as a self -administered tool for the evaluation of differences in symptom severity and health related quality of life in patients. The aim of this study was to determine if the USgHIFU treatment applied on a South African population improved the symptoms and quality of life perceived by patients. This study was a retrospective analysis of prospectively collected data collected from 116 women from 1 October 2015 to September 2016 at Chris Hani Baragwanath Academic Hospital gynaecological department. Patients were interviewed before and at 6-months post treatment, using the UFS-HQOL questionnaire to identify the various symptoms and gauge the severity thereof. The study consisted of women with mean age 34.95 ± 5.97 years with mean weight of 67.67 ± 0.64 kg and 35.34% being overweight. A total of 87% of women at baseline exhibited some form of dysmenorrhea, in comparison to 73% of women at 6-months. The UFS subscale (heavy bleeding during menstrual periods; fatigue; pelvic pressure; urination frequency) showed a mean score for symptom severity of 25.5 ±16.4 at the initial stage, improving to 15.5 ± 9.3 at the 6 months post treatment (higher scores highlight a greater number of symptoms and greater distress). The HRQL aspect (concern; activities; energy/mood; control; self-consciousness; sexual function) provided patterns of perceived improvement in all aspects at month 6 (total HRQL score of 77± 16.9, change mean score 35.8 and effect size of 1.8).Therefore the questionnaire was able to detect and record the improvement of the health quality related and associated aspects of the lives of women6 months post USgHIFU treatment
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in Obstetrics and Gynaecology, 2021